The Role of Public Health Provider on Improving of the Mother’s Knowledge and Awareness on Covid 19 for Her Children - Sugeng Eko Irianto; Dian Utama Pratiwi Putri; Tubagus Erwin Nurdiansyah (LPPM STIKES KENDAL, 2021)
During time of COVID-19 pandemic, women are often burdened with greater expectation to carry out domestic responsibilities, including tending to children and ill members of the family. With school closures and disruptions at the workplace becoming the norm, including working from home, there is bound to be more expectations from women responsibility. Health education on COVID-19 by public health providers to the women/mother was conducted to improve the knowledge and awareness of the women itself and the family members by using digital technology/tele-education. There were challenges for the public health worker such as technical skill of case management, clinical management, and others. To address the challenges, the government implemented a strategic approach at individual level, organization level, and systemic level.